Rotation and translation: The meaning of life as a potential educational resource - Javier Bermejo Fernández-Nieto (Ricerche di Pedagogia e Didattica)
This article sets out to analyse how such a polysemic and subjective concept as the meaning of life can be addressed in educational terms. To do so, it starts from the conceptualisation of the term, framing it in the experiential plane, understanding that this experience develops both internally (rotation) and externally (translation). This is followed by the presentation of two core approaches based on which pedagogical proposals have recently been constructed. The first of these is based on the approach centred on narrative identity in both its classical aspect and its version linked to life history. The second is based on moral development, mainly using dilemmas as a didactic resource. Finally, the article addresses the framing of these considerations within the horizon of current educational philosophy, reflecting on the relevance of the same in the particular framework of its practice.